Green Practices and Purchase Intentions: The Mediating Role of Green Image and Trust Among Muslim Consumers - M Qoshid Al Hadi; Wahab, Abdul; Budi, Iman Setya (Global Review of Islamic Economics and Business, 2024)
The issue of sustainability of green products has garnered significant attention within both societal and business spheres. In essence, green products constitute a crucial consideration in marketing. The development of various marketing methods has contributed to diverse public perceptions as well as eco-friendly products widely available on the market. Therefore, this study aimed to determine the influence of green practice, green image, green trust, and purchase intention. Furthermore, this study also investigated green image and green trust as a mediator in the relationship between green practices and purchase intention while also exploring the moderating role of environmental awareness in this relationship.  A total of 393 Muslim consumers from 10 provinces with the largest Muslim majority in Indonesia were selected to fill out an online questionnaire. The collected data was processed using AMOS-v26 and SPSS v25. The results demonstrated that green image and green trust mediate the relationship between green practices and green purchase intention. Meanwhile, environmental awareness was found to moderate the indirect relationship among the variables of green practices, green image, green trust, and green purchase intention. These findings contribute to the strengthening of self-congruity theory. This study also contributes to theoretical and contextual knowledge related to the perceptions and behavior of Muslim consumers regarding the consumption of green products, offering valuable business considerations for practitioners.